Pretreatment and enzymatic hydrolysis of sunflower hulls for fermentable sugar production - Kamireddy, Sirinivas R.; Schaefer, Christopher; Defrese, Matt; Degenstein, John; Ji, Yun (International Journal of Agricultural and Biological Engineering, 2012)
Abstract: Sunflower is a widely adapted crop and can be grown in every temperature region. In the U.S., two million acres were cultivated with sunflowers in 2009. During industrial processing, large quantities of hulls are obtained as a waste product from the dehulling process. This study focused on converting the sunflower hulls into fermentable sugars by dilute acid pretreatment and enzymatic hydrolysis. Raw sunflower hulls are composed of